A Sensorless PM Synchronous Motor Drive for Electric Washers - Filka, R.; Balazovic, P.; Dobrucky, Branislav (Communications - Scientific letters of the University of Zilina, 2007)
This paper presents a complex solution for whole speed range sensorless control of interior permanent magnet synchronous motor drives. To cover an entire speed range of IPMSM without position transducer, different sensorless techniques must be employed. Design and implementation of sensorless techniques for different operating speeds are described in this paper. Presented application has been implemented including the high frequency (hf) injection method and extended back EMF state observer on a single chip solution of DSC56F8300 series without any additional supportive circuitry. The extended back EMF algorithm with angular speed and position observer is suitable for sensorless control drive. It is also transferable for other motor types, e.g. synchronous reluctance- or synchronous one with ‘smooth’ rotor. The presented sensorless control has been proved in electric washer drive with very good operating properties.